Ramona the pest - Cleary, Beverly; Darling, Louis (New York : Morrow Junior Books, 1968)
Ramona meets lots of interesting people in kindergarten class, like Davy whom she keeps trying to kiss and Susan whose springy curls seem to ask to be pulled.
R
850
R
Keywords: Kindergarten -- Fiction; Schools -- Fiction; Juvenile literature -- 1968.